THE EFFECTIVENESS OF THE E-SAMBAT APPLICATION IN IMPROVING THE QUALITY OF SERVICE AND COMMUNITY COMPLAINTS (STUDY AT THE PASURUAN CITY COMMUNICATION, INFORMATICS AND STATISTICS OFFICE) - Dwinta, Elzha Cindi; Mursyidah , Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the e-Sambat application in enhancing the quality of public complaint services in Pasuruan City and to identify supporting and inhibiting factors in its implementation. Method: A descriptive qualitative method with an inductive approach was employed, using Gibson’s (2011) effectiveness framework and Zeithaml et al.’s service quality dimensions (in Hiplunudin, 2017). Data were collected through observations, in-depth interviews, and documentation to capture both process and outcome dimensions. Results: The findings indicate that the e-Sambat application plays a significant role in streamlining the public complaint process and has contributed positively to service quality, particularly in terms of responsiveness and reliability. Nevertheless, the limited number of users remains a major obstacle, largely due to insufficient socialization and system optimization. Despite these challenges, the services provided through e-Sambat are perceived as satisfactory and capable of addressing various community complaints effectively. Novelty: This research provides new insights into the role of digital complaint systems at the municipal level, highlighting e-Sambat not only as an administrative innovation but also as a strategic instrument for improving citizen engagement and fostering sustainable public service transformation.